Morphology-controlled synthesis of nanosphere-like NiCo2S4 as cathode materials for high-rate asymmetric supercapacitors. (1st June 2018) - Chen, Yin-Ying; Dhaiveegan, Periyathambi; Michalska, Monika; Lin, Jeng-Yu
Abstract: In this study, we successfully synthesized nanosphere-like NiCo2 S4 (NCS) materials via one-pot polyvinylpyrrolidone (PVP)-assisted hydrothermal method, and directly were employed as cathode materials for asymmetric supercapacitors (ASCs). It is found that the surface morphology of the NCS materials can effectively tuned from the irregular to nanosphere-like shape along with the reduced particle size by simply altering the concentration of PVP contents. After the optimization of the PVP concentration, the resultant NCS electrode delivered remarkable specific capacity up to 82.6 and 46.2 mAh g −1 at a current density of 1 and 16 A g −1, respectively. Additionally, an ASC fabricated by employing the nanosphere-like NCS as the cathode and graphene hydrogel (GH) as anode demonstrated a high energy density of 23.8 Wh kg −1 at a power density 1016.5 W kg −1 . More importantly, the as-assembled ASC retained 91.4% of its initial capacity after charged/discharged at 8 A g −1 for 5000 cycles, signifying its excellent cycling performance. Graphical abstract: Image 1